Different stages of maturity and times of bagging in relation to quality of coffee - Lima Angélico, Caroline; Pimenta, Carlos José; Chalfoun, Sára Maria; de Resende Chagas, Sílvio Júlio; Cláudio Pereira, Marcelo; Chalfoun, Yasmin (Coffee Science - ISSN 1984-3909, 2011)
Although causing extensive damage, bagging coffee cherries before drying occurs even in the field due to adverse factors soon after boltering, such as rain during the harvest, problems during transport to the drying area or even the poor plantation design, besides the lack of mechanical dryers for most small producers, thus requiring a more scientific foundation. Given this fact, the aim of this study was to evaluate the real effect of this practice on the quality of coffee in different stages of maturation, bagging from up to four days before drying, and to verify the behavior of different stages with regard to this procedure. Physical, chemical, and physicochemical analysis as well as classification according to type and drink were performed using Acaiá coffee fruits (Coffea arabica L.) collected at Perdões - MG and separated by hand after picking, in four maturation stages (green / greenish yellow, cherry, dried pruns and fruit mixture). After separation, they were packed in polyethylene bags and subjected to five bagging times ranging from 0, 1, 2, 3 and 4 days. After each period, samples were dried in a concrete yard for analysis. The analysis results showed that the electrical conductivity parameters, leaching of potassium and PPO activity were shown to be as important quality markers. Taste tests classified most treatments as “hard coffee”. Based on these results it was found that bagging promoted loss of bean quality from the first day